Opiate receptors influence vasopressin release from nerve terminals in rat neurohypophysis. - Iversen, L; Iversen, S; Bloom, F (1980)
A previous report described the existence of substantial amounts of enkephalin immunoreactivity and the occurrence of nerve terminals containing an enkephalin-like material in the pars nervosa of rat pituitary. It was suggested that an enkephalin innervation of the pars nervosa originating from the magnocellular hypothalamic nuclei might regulate the secretion of neurohypophyseal hormones. The results of the present studies support this hypothesis, as we find that a stable enkephalin analogue (D-Ala 2,D-Leu5-enkephalin) inhibits the calcium-dependent release of vasopressin evoked by electrical stimulation of the rat pituitary stalk in vitro. A similar inhibition of the stimulus-evoked vasopressin release is caused by morphine and beta-endorphin, and the inhibitory effects of the enkephalin analogue can be reversed by naloxone. These findings suggest the possible existence of inhibitory opiate receptors on the terminals of vasopressin fibres in the pars nervosa.